Dakwah di Era Digital: Tantangan Sosiologis dan Solusinya - Nazar Naamy (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2023)
The development of digital technology has transformed the landscape of dakwah practices in society. This article investigates the sociological challenges faced in dakwah practices in the digital era and seeks solutions to overcome these challenges. The research aims to identify sociological challenges related to dakwah in the digital era and formulate solutions to address these challenges. The research method employed is a literature review using a descriptive-analytical approach. Data were obtained through the analysis of scholarly literature, journal articles, books, and other relevant sources discussing dakwah in the digital era. Data analysis detailed the sociological challenges encountered in digital dakwah practices, such as shifts in communication paradigms and the dissemination of unverified religious content. Proposed solutions to address these challenges were also analyzed to assess their potential for successful implementation. The results of this research indicate that dakwah practices in the digital era face significant changes in how religious communication is conducted, along with the risk of spreading extremist views. Proposed solutions, such as leveraging digital technology and collaboration between religious institutions and technology platforms, have the potential to address these challenges. Dakwah in the digital era faces sociological challenges that need to be addressed to ensure its relevance and effectiveness. The suggested solutions, if well-implemented, can help maintain a moderate, tolerant, and peaceful approach to dakwah in society. This research has practical implications for preachers and religious institutions in understanding the changes in dakwah practices in the digital era. Furthermore, the research findings can assist technology platforms in monitoring religious content and preventing the spread of extremist views. These implications can contribute to the promotion of peace and tolerance in an increasingly digitally connected society.